Cross-country comparison of EFL teacher preparedness to include dyslexic learners: Validation of a questionnaire - Nijakowska, Joanna; Tsagari, Dina; Spanoudis, George (Studies in Second Language Learning and Teaching, 2020)
The aim of this study was to validate a 24-item TEPID (Teachers of EFL Preparedness to Include Dyslexics) scale measuring the beliefs of 546 pre-service and in-service teachers of English as a foreign language (EFL) across three countries (Cyprus, Greece, and Poland) on their preparedness to include learners with dyslexia in mainstream foreign language (FL) classes. Principal component analysis of the scale led to a two-factor structure, that is, knowledge and self-efficacy in implementing inclusive instructional practices with dyslexic EFL learners, and stance towards inclusion. The analysis of measurement invariance confirmed the generalizability of the TEPID across all subgroups and allowed valid comparisons between factor variances and covariances. The scale is a useful tool for investigating perceived teacher preparedness to include dyslexic learners and variables that influence TEPID, comparing the results across countries, and designing tailored pre-service and in-service training schemes on inclusion.